Coexistence in a subtidal habitat in southern Chile: the effects of giant kelp Macrocystis pyrifera overgrowth on the slipper limpet Crepipatella fecunda. (February 2015) - Díaz, Francisco J.; Pereda, Sandra V.; Buschmann, Alejandro H.
<x content-type="archive" xml:space="preserve">Abstract</x> In many coastal areas substrate is the limiting resource for benthic organisms. Some sessile species can be used as secondary substrate, reducing competition and increasing coexistence. In southern Chile, annual populations of Macrocystis pyrifera recruit and grow on the shells of Crepipatella fecunda. This study describes ecological interactions between the kelp and the slipper limpet over an annual cycle. The degree of kelp overgrowth was established by collecting sporophytes and through in situ submarine photography over a 10 month period (starting when kelp recruits became visible and ending when sporophytes were no longer present). Changes in the biochemical composition of the limpet tissue were also recorded by chemical analyses, to evaluate the potential effects (positive/neutral/negative) of kelp on C. fecunda nutritional condition. The results indicate that both species coexist, although kelp overgrowth may cause a decrease in carbohydrates in C. fecunda tissues, restricted to the period when the kelp forest reaches its maximum biomass. Individually, the short duration of the maximum overgrowth period and the size reached by C. fecunda females (up to 65 mm shell length) may enable rapid limpet recovery, avoiding competitive exclusion. On a population level, the M. pyrifera annual cycle generates the needed 'break' for C. fecunda populations, reducing the effects of kelp overgrowth. Thus, in the view of the neutral effect of kelp overgrowth, together with the positive effect of C. fecunda on M. pyrifera recruitment described somewhere else, this ecological interaction can be categorized as commensalism.